How chromosomal deletions can unmask recessive mutations? Deletions in 10q11.2 associated with CHAT or SLC18A3 mutations lead to congenital myasthenic syndrome. Issue 1 (12th November 2017) - Schwartz, Mathias; Sternberg, Damien; Whalen, Sandra; Afenjar, Alexandra; Isapof, Arnaud; Chabrol, Brigitte; Portnoï, Marie‐France; Heide, Solveig; Keren, Boris; Chantot‐Bastaraud, Sandra; Siffroi, Jean‐Pierre
Abstract : A congenital myasthenia was suspected in two unrelated children with very similar phenotypes including several episodes of severe dyspnea. Both children had a 10q11.2 deletion revealed by Single Nucleotide Polymorphisms array or by Next Generation Sequencing analysis. The deletion was inherited from the healthy mother in the first case. These deletions unmasked a recessive mutation at the same locus in both cases, but in two different genes: CHAT and SLC18A3 .